2015
DOI: 10.1002/pmic.201400472
|View full text |Cite
|
Sign up to set email alerts
|

Protein 2DE reference map of the anterior midgut of the blood‐sucking bug Rhodnius prolixus

Abstract: Rhodnius prolixus is an important vector of Trypanosoma cruzi, the causative agent of Chagas' disease, an illness that affects 20% of Latin America population. The obligatory course of the parasite in the vector digestive tract has made it an important target for investigation in order to control the parasite transmission and thus interrupt its biological cycle in the insect vector. Therefore, an insight into the vector midgut physiology is valuable for insect control as well as to provide potential novel targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(33 citation statements)
references
References 20 publications
(26 reference statements)
2
29
1
Order By: Relevance
“…In this study, we reported the analysis of the midgut proteome of R. prolixus using high-throughput proteomic analysis tools. These data are complementary to the R. prolixus digestive tract transcriptomic data reported by Ribeiro et al, 2014 [ 14 ], and the 2-DE reference map of the AM of the insect [ 43 ]. The expression of several proteins for which transcripts are highly expressed in the midgut has been confirmed by our study at the protein scale, such as proteases and protease inhibitors.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In this study, we reported the analysis of the midgut proteome of R. prolixus using high-throughput proteomic analysis tools. These data are complementary to the R. prolixus digestive tract transcriptomic data reported by Ribeiro et al, 2014 [ 14 ], and the 2-DE reference map of the AM of the insect [ 43 ]. The expression of several proteins for which transcripts are highly expressed in the midgut has been confirmed by our study at the protein scale, such as proteases and protease inhibitors.…”
Section: Discussionsupporting
confidence: 72%
“…Since no proteolytic digestion has been detected in the AM [ 42 ], the presence of cathepsins in this part of the midgut was suggested to be in the form of proenzymes, which are further activated in the PM [ 13 , 14 ]. Interestingly, a 2-DE reference map of the AM of R. prolixus identified four processed forms of cathepsins, suggesting that these enzymes could be maturated in the AM [ 43 ]. Hence, to validate this observation, we tested cathepsins D activities in both R. prolixus AM and PM protein extracts 6 h after a blood meal by using a fluorogenic substrate specific to cathepsin D at acidic pH.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of the search for proteins possibly implicated in the triatomine immune system, we also detected three annexins (described initially in R. prolixus) in our proteome samples. After comparing these three annexins with sequences from Ribeiro et al (2014), Vieira et al (2015) and Ouali et al (2020) through Basic Local Alignment Search Tool (BLAST) analyses, we noted that these authors already found them confirming previous inferences from the complete genome sequence. Annexins are a family of proteins that are associated with many biological events, including calcium-binding, interaction with membranes, intracellular vesicle trafficking, arachidonic acid release, leukocyte migration, and that also affects several mediators involved in the inflammatory response including cyclo-oxygenase-2 (Cox-2) and inducible nitric oxide synthase (Minghetti et al, 1999;Ferlazzo et al, 2003;Rescher and Gerke, 2004;Gavins and Hickey, 2012).…”
Section: Introductionsupporting
confidence: 68%
“…To integrate the proteome of this study to previous knowledge, we gathered the sequences from our proteome samples with the datasets of R. prolixus from Ribeiro et al (2014), Vieira et al (2015) retrieved from the Bioinformatics Resource for Invertebrate Vectors of Human Pathogens (VectorBase, 4 ), and Ouali et al (2020) from ProteomeXchange Consortium. We retrieved the equivalent of UniprotKB accession considering an identity region (BLASTp) of 70% of the query sequence with a similarity ≥ 80% in the case of sequences from Ribeiro et al (2014) and Vieira et al (2015). Since the sequences from Ouali et al (2020) were already given with UniprotKB accessions, this exercise was not necessary.…”
Section: Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation